Working life expectancy in good and poor self-perceived health among Dutch workers aged 55–65 years with a chronic disease over the period 1992–2016. Issue 11 (7th September 2018) - de Wind, Astrid; van der Noordt, Maaike; Deeg, Dorly J H; Boot, Cecile R L
Abstract : Objectives: Several governments have taken measures to encourage prolonged working. It is therefore likely that older adults with a chronic disease are required to work longer in poor self-perceived health (SPH) than before. This study examines to what extent working life expectancy (WLE) in good and poor SPH changed between 1992 and 2016 in workers with a chronic disease from age 55 years onwards. Methods: Three cohorts (1992, 2002 and 2012) of workers with a chronic disease aged 55–65 years were selected from the Longitudinal Aging Study Amsterdam with a 3-year follow-up each (n=705). A three-state survival model was estimated, modelling transitions between states 'working with good SPH', 'working with poor SPH' and 'exit from work'. WLEs were estimated using Multistate Modelling and Estimating Life Expectancies using Continuous Time in R. Results: Of the workers with a chronic disease, total WLEs at age 55 years were 5.2, 5.7 and 6.8 years in cohorts 1992, 2002 and 2012, respectively. Workers initially having poor SPH, had total WLE of 4.7 years of which 2.4 years in poor SPH in cohort 1992. These workers had total WLE of 5.2 years of which 3.3 years in poor SPH in cohort 2002, and total WLE of 6.5 years of which 3.6 years in poor SPH in cohort 2012. Conclusions: Workers with a chronic disease extended their working lives by approximately 18 months from 1992 to 2016. In the first decade, unhealthy WLE increased, whereas in the second decade, healthy WLE increased, among both workers in general and workers initially having poor SPH.